Examining Social Media Addiction as a Predictor of Academic Achievement and Academic Procrastination: A Cohort of Undergraduate Students - Suleyman Avci; Mustafa Cakir; Tuncay Akinci (Journal on Efficiency and Responsibility in Education and Science)
This study aims to examine the effects of self-control and future time perception on social media addiction and academic procrastination and determine whether social media addiction affects academic achievement through academic procrastination. A total of 559 university students participated. The participants’ most commonly used social media platforms were WhatsApp and Instagram. Path analysis technique was used to analyze the theoretical model. In the theoretical model created to test the 13 hypotheses in the research, future time perception (value, distance, commitment, and speed) and self-control are exogenous variables, social media addiction and academic procrastination are moderating variables, and academic achievement is endogenous variable. According to the research findings, social media addiction is not a significant predictor variable for either academic achievement or academic procrastination. Self-control and speed are significant predictors of both social media addiction and academic procrastination. Commitment predicts social media addiction, and value predicts academic procrastination. On the contrary, value is not a significant predictor of social media addiction, and commitment is not a significant predictor of academic procrastination. Distance is not a significant predictor of social media addiction or academic procrastination.